Habitat and Experience: An Anthropology of the Sonic Agglomeration - Schulze, Holger (Kulturstudier, 2021)
This contribution provides a contemporary introduction into research and artistic practices related to the study of sonic agglomerations from the perspective of an anthropology of sound. The article has four parts within which its author traverses and experiences an agglomeration such as Copenhagen by employing the very methods, practices and explorative approaches that are introduced in this article. Starting with “Spatial Volumes, Secluded and Eroding“ (part 1), the author focuses then on “Protocol and Dérive“ (part 2), „The Noise of the Other“ (part 3), “An Escape to Recreate” (part 4) and asks toward the end the question “What Might a City Be?” In this way the urban sonic experience is unfolded through recent research approaches within or close to the field of sound studies.